Molecular diagnosis of hen eggs microbiota: Molecular diagnosis of microbiota - Al-Hejin, Ahmed M.; Ahmed, Mohamed Morsi M.; Alattasa, Sana Ghazi; Al Karaim, Saleh (Cellular and Molecular Biology, 2024)
The study was conducted in the Kingdom of Saudi Arabia from 2020 and 2022. The identification, characterization, and evaluation of microbes found in hen eggs was done and it was found very important to prevent contamination caused by various harmful pathogenic microbes. It was found that contaminated eggs harbor various harmful microbes which affect health due to multiple infectious diseases. Hen eggs contain a wide variety of microbes, and several distinct approaches were utilized as well as available for achieving detailed pathogenic information. The information obtained is highly essential for people who consume eggs as a food product. It is of the utmost importance to protect people from getting sick due to the consumption of contaminated eggs or eggs from chickens that have been infected by various harmful pathogens. During the experiment, we found that eggs were contaminated directly or the chicken that laid the egg was contaminated. Using molecular genetic analysis, it is possible to detect pathogenic and non-pathogenic contaminations in eggs. During present studies, the cutting-edge molecular techniques of 16S rRNA gene sequencing technology were used to carry out the objective of performing a molecular identification of the microbial communities infecting eggs. The present research is aimed at determining whether the microbial communities in hen eggs are harmful to humans. The results further indicated most bacteria have the potential to cause illness in humans including Escherichia fergusonii, Salmonella enterica, Pseudocitrobacter faecalis, Yakenella regensburgei, and Erwinia pyrifoliae. Further, research suggested that eggs need to be properly cooked and thoroughly washed to eliminate the possibility of consuming infected eggs.